Hospitalized poisonings after renal transplantation in the United States - Viola Rebecca A; Abbott Kevin C; Agodoa Lawrence Y (BMC Nephrology, 2002)
Abstract Background The national incidence of and risk factors for hospitalized poisonings in renal transplant recipients has not been reported. Methods Historical cohort study of 39,628 renal transplant recipients in the United States Renal Data System between 1 July 1994 and 30 June 1998. Associations with time to hospitalizations for a primary diagnosis of poisonings (ICD-9 codes 960.x-989.x) within three years after renal transplant were assessed by Cox Regression. Results The incidence of hospitalized poisonings was 2.3 patients per 1000 person years. The most frequent causes of poisonings were immunosuppressive agents (25.3%), analgesics/antipyretics (14.1%), psychotropic agents (10.0%), and insulin/antidiabetic agents (7.1%). In Cox Regression analysis, low body mass index (BMI, <21.6 vs. >28.3 kg/m2, adjusted hazard ratio (AHR), 3.02, 95% CI, 1.45–6.28, and allograft rejection, AHR 1.83, 95% CI, 1.15–2.89, were the only factors independently associated with hospitalized poisonings. Hospitalized poisonings were independently associated with increased mortality (AHR, 1.54, 95% CI 1.22–1.92, p = 0.002). Conclusions Hospitalized poisonings were associated with increased mortality after renal transplantation. However, almost all reported poisonings in renal transplant recipients were due to the use of prescribed medications. Allograft rejection and low BMI were the only independent risk factors for poisonings identified in this population.